New Electron Conversion Lines from Existing ?-Transitions In 160dy - D.D., Bogachenko; Egorov, Oleg Konstantinovich; V.P., Garistov; V.V., Kolesnikov; V.I., Silaev; A.A., Solnyshkin (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Three photo plates derived with spectrograph LNP JINR with constant magnetic field [1] have been investigated using the Microscope Automatic Scanning MAS [2]. Electron internal conversion (ICE) spectrograms of two erbium (Er P-2, Er P-8) and one Ho fractions has been measured. More detailed analysis gave us the possibility to obtain some new lines (see table) in addition to many earlier existing lines in 160Dy [3]. For that investigations it is necessary to increase the speed with which microscopic objects are measured are described. These efforts include the modernization of the MAS automatic scanning microscope and the development of programs to reach an initial point and for carrying out automatic point-to-point linear transitions with a specified step. The error in realizing a transition to a given point with specified coordinates is shown to amount to 1 µm.